Routines, values and other influences in the production of news: The testimony of four managing editors in Monterrey, Mexico (Communication & Society, 2010)
In order to provide information about the organizational influences affecting the production of news in Mexico, this paper discusses the testimonies of four managing editors of print and electronic news media during the 1980´s in Monterrey, Mexico. Based on in-depth interviews, the study provides evidence on the complex processes of negotiation and degrees of autonomy of Mexican managing editors of newspapers and television newscasts in relation to the economic and ideological interests of media owners and of the local economic and political elite. In addition, the study identifies the main work routines and individual characteristics influencing and shaping the content of local news.